A Umbanda esotérica e seu processo educativo: caminhos de superação do racismo religioso - Alcides Junio Silva Lopes (2022)
This research investigates the construction of educational processes based on my experience in an Esoteric Umbanda Terreiro in Esmeraldas/MG. I try to reflect on the possible pedagogical contributions of Umbanda to the promotion of inter-religious dialogue and the construction of a network of resistance from its subjects, aiming to build social relations to overcome the religious racism present in our society. This paper has a wide range of theoretical references from Ferdinand Röhr (2011, 2013) work, considering especially his approach to the multidimensionality of man and reality. Stuart Hall (2006) highlights the subject's issue identification, and Jessé Souza (2021), with his multidimensional and multicultural approach to racism. Considering the methodological option work was based on ethnographic and autoethnographic qualitative research; permeated by the writing, a term coined by Conceição Evaristo (2020); and by participant research. We also used bibliographic research, and semistructured interviews with participants of Tenda de Umbanda Oriental Senhores de Aruanda's temple, in addition to the reflections arising from the researcher's experience as a priest in the Esoteric Umbanda Terreiro. An audio-visual pedagogical resource format was created, where we seek to present the testimony of some Umbanda practitioners regarding religious racism from their own experiences.